Deciphering the role of Saliva in COVID 19: A global cross-sectional study on the knowledge, awareness and perception among dentists - Selvakumar Kritika; Sekar Mahalaxmi; N Srinivasan; Jogikalmat Krithikadatta (BMC, 2023)
Abstract Objectives The global pandemic outbreak of the coronavirus has instilled the quest amongst researchers on the expedited need for the early detection of viral load. Saliva is a complex oral biological fluid which not only causes the disease transmission but can be an effective alternative sample for detection of SARS-CoV2. This provides an ideal opportunity for dentists to be the frontline healthcare professionals who can collect the salivary samples; however the awareness of this amongst dentists is uncertain. Hence the aim of this survey was to evaluate the knowledge, perception and awareness of the role of saliva in detecting the SARS-CoV2 among dentists worldwide. Methods The online questionnaire comprising of 19 questions was shared to 1100 dentists worldwide and a total of 720 responses was collected. The data was tabulated, statistically analysed using the non- parametric Kruskal-Wallis test (p < 0.05). Based on the principal component analysis, 4 components (knowledge about virus transmission, perception about SARS-CoV2 virus, awareness on the sample collection and knowledge about prevention of the virus) were obtained which was compared with the 3 independent variables (years of clinical experience, occupation and region). Results A statistically significant difference was observed in the awareness quotient amongst the dentists with 0-5 years and greater than 20 years of clinical experience. In terms of the occupation, a significant difference was noted when comparing the postgraduate students to practitioners knowledge about the virus transmission. A highly significant difference was seen on comparing academicians and postgraduate students and also between academicians and practitioners. No significant difference was evidenced amongst the different regions, however the mean score was in the range of 3-3.44. Conclusion This survey highlights the deficiency in the knowledge, perception and awareness among dentists worldwide.